Entrapment of Chlorella vulgaris cells within graphene oxide layers - Wahid, M.; Eroglu, Ela; Chen, X.; Smith, S.; Raston, C. (2013)
Confinement of microalgae cells within layers of graphene oxide (GO) effectively reduces the rate of cell division, with the microalgal wrapping being more efficient in a vortex fluidic device than using mild sonication, as determined by the cell growth and the level of nitrate removal from the liquid effluent. © 2013 The Royal Society of Chemistry.